Death & the viking's daughter [large type] - Ross, Loretta, 1966- (An auction block mystery, 2018)
Auctioneer Wren Morgan and her private eye fiancé Death (pronounced "Deeth") Bogart are ready to meet each other's parents and settle down together. But their sleuthing days are far from over. While Death and Wren are helping prepare auction items at an old supper club, a Viking reenactor nearly dies at the historical settlement next door. The cause? Seeing the ghost of his daughter, who went missing twenty years ago.